TECHNIQUES FOR PSYCHOLOGICAL COUNSELLING OF INDIVIDUALS WITH VIOLENT AND VICTIMISING BEHAVIOUR - Ivanov, Krasimir; Petkova, Pavlina (E-Journal VFU, 2025)
The article provides information on current techniques for diagnosis and psychological counseling of individuals with aggressive behavior. The different areas of therapeutic influence are presented and the algorithm of the diagnostic and consultative process is explained.
Keywords: psychological counseling; aggressive behavior; psychodiagnostics; emotions; therapeutic process